Innovative Approaches in ESL to Enhance Motivation and Attitude Through Technology Integration - Nor Fadhilah Ahmad Powzi; Lina Zainal (Development in Language Studies, 2024)
The study was conducted to identify major problems students of a tertiary institution in the Southern part of Malaysia face in learning the English Language. A survey via Padlet was conducted to find out students’ opinions on the current classroom teaching and learning instructions. Most respondents stated that they find the conventional method of classroom instruction uninteresting and dull. The students also mentioned that they wished to have more technological tools incorporated into the classroom. Therefore, a lesson that incorporated the use of Quizizz and Kahoot was conducted on the topic of Job Interview. Students responded positively to the lesson. This suggests that educators should consider the incorporation of technological tools in the classroom, such as Quizizz and Kahoot, to boost students’ motivation and positive attitudes towards English language learning.